Vestigios en castellano de antiguos giros sumerios y acadios a través de los textos bíblicos latinos y sus modelos griegos y hebreos - Jiménez Zamudio, R. (ISIMU, 2016)
In this paper the author proposes that in Spanish we can find a large number of expressions characterized as prepositional periphrases such as "ante la faz de", "ante los ojos de", "a oídos de", "a espaldas de". Such expressions were intoduced into Spanish through several translations of biblical Latin. Nevertheless their origin and deep meaning must be sought in the social context of the biblical texts themselves: that is, within a society whose world view was very homogeneous and was made up of a great number of people of the Ancient Near East, many of them spoke different languages. Besides Classical Hebrew, Sumerian and Akkadian were outstanding and had a decisive influence on them.